An NR2B-Dependent Decrease in the Expression of trkB Receptors Precedes the Disappearance of Dopaminergic Cells in Substantia Nigra in a Rat Model of Presymptomatic Parkinson's Disease - Eduardo Riquelme; Jorge Abarca; Jorge M. Campusano; Gonzalo Bustos (Parkinson's Disease)
Compensatory changes occurring during presymptomatic stages of Parkinson's disease (PD) would explain that the clinical symptoms of the disease appear late, when the degenerative process is quite advanced. Several data support the proposition that brain-derived neurotrophic factor (BDNF) could play a role in these plastic changes. In the present study, we evaluated the expression of the specific BDNF receptor, trkB, in a rat model of presymptomatic PD generated by intrastriatal injection of the neurotoxin 6-OHDA. Immunohistochemical studies revealed a decrease in trkB expression in SN pars compacta (SNc) seven days after 6-OHDA injection. At this time point, no change in the number of tyrosine hydroxylase (TH) immunoreactive (TH-IR) cells is detected, although a decrease is evident 14 days after neurotoxin injection. The decrease in TH-positive cells and trkB expression in SNc was significantly prevented by systemic administration of Ifenprodil, a specific antagonist of NR2B-containing NMDA receptors. Therefore, an NR2B-NMDA receptor-dependent decrease in trkB expression precedes the disappearance of TH-IR cells in SNc in response to 6-OHDA injection. These results support the idea that a functional coupling between NMDA receptors and BDNF/trkB signalling may be important for the maintenance of the dopaminergic phenotype in SNc during presymptomatic stages of PD.